NorthBEAT: exploring the service needs of youth experiencing early psychosis in Northern Ontario - Cheng, Chiachen; Nadin, Shevaun; Bohonis, Hafsa; Katt, Mae; Dewa, Carolyn S. (Frontiers in Health Services, 2023)
Early Psychosis Intervention (EPI) is critical for best outcomes Among 369 diseases, psychosis is among those causing the greatest disability. Evidence-based interventions for youth in early stages of psychosis (EPI programs) have prevented chronic disability. Yet, EPI is frequently inaccessible for youth living in rural communities. Moreover, Indigenous youth often face more precipitous situations given inadequate staffing, insufficient funding and culturally unsafe care. The NorthBEAT (Barriers to Early Assessment and Treatment) project sought to understand the service needs of youth with psychosis in Northern Ontario. NorthBEAT 1) described the mental health of a subset of adolescents receiving EPI care; 2) examined Indigenous youth as a significant and vulnerable population; 3) sought to understand the barriers and facilitators for Indigenous and non-Indigenous youth receiving EPI. Methods Mixed methods (structured and narrative interviews) included: youth were assessed using psychometric scales, narrative interviews were conducted with youth, their family, and service providers Data validation workshops were held with participants. Results Structured interviews with 26 youth (M=17 years) found the participants functioning moderately well with a duration of untreated psychosis ranging from 1-96 months (M=26 months). No significant differences were found in functioning or duration of psychosis between Indigenous and non-Indigenous youth. Narrative interviews were conducted with 18 youth, 11 family members, and 14 service providers. I d e n t i f i e d b arriers were a lack of knowledge about psychosis among service providers, a disconnected system leading to delays in treatment, help not wanted by youth, expansive geographical context. Service needs were: finding the right point of access, support for families, p r e - c r i s i s intervention, reduced stigma for youth and their families, and an EPI approach to care. Discussion Rural and northern youth face similar barriers to accessing EPI as urban youth. However, n o r t h e r n youth face